DNA Imprinting and Differentially Expressed Genes in Longissimus thoracis Muscle of Bos indicus Submitted to Early Weaning Management - Tinoco, Gustavo [UNESP]; Russo, Gustavo [UNESP]; Curi, Rogério [UNESP]; Vicari, Marcelo; Melo, Paloma [UNESP]; Souza, Isabella [UNESP]; Torrecilhas, Juliana [UNESP]; Moriel, Philipe; Baldassini, Welder [UNESP]; Chardulo, Luis [UNESP]; Neto, Otávio [UNESP]; Pereira, Guilherme [UNESP] (MDPI, 2024)
Background/Objectives: Early weaning management followed by energy supplementation can lead to metabolic alterations in the calf that exert long-term effects on the animal’s health and performance. It is believed that the main molecular basis underlying these metabolic adaptations are epigenetic mechanisms that regulate, activate, or silence genes at different stages of development and/or in response to different environmental stimuli. However, little is known about postnatal metabolic programming in Bos indicus. Therefore, this study aimed to compare the DNA methylation profile of Nellore animals submitted to conventional and early weaning and to correlate the findings with genes differentially expressed in the Longissimus thoracis skeletal muscle of Bos indicus cattle. Methods: For this, we used Reduced Representation Bisulfite Sequencing (RRBS) and RNA-Sequencing techniques to prospect differentially methylated genes (DMGs). Results: A total of 481 differentially methylated regions were identified, with 52% (250) being hypermethylated and 48% (231) hypomethylated. Functional enrichment analysis of 53 differentially methylated and differentially expressed genes was performed. The main enriched terms and pathways were associated with 3′-5′-cyclic adenosine monophosphate (cAMP) signaling, which presents the upregulated adenylate cyclase 3 (ADCY3) gene and significatively hypomethylated in the promoter region. Alterations in cAMP signaling are involved in numerous processes, many of them related to lipid metabolism. The relative differential expression of key genes of this pathway demonstrates the relationship between cAMP signaling and de novo lipogenesis. Conclusions: These findings suggest an important role of postnatal metabolic programming through DNA methylation mechanisms in determining fat deposition in beef.
Keywords: adipogenesis; early weaning; epigenetics; meat